Sexual Harassment Myths and Victims’ Blame Game among the Students of Institutions of Higher Learning: Implication to Gender-based sexual Violence and Community/Sustainable Development in Southeast Nigeria - Okafor, Samuel; Ekwealor, Nwakaego; Nkemjika, Ogechi; Anekeje, Ukamaka; Ogechi, Ikem; Egbe, Adaobi (Journal of International Students, 2023)
The study investigated the issue of sexual harassment myths among the students of higher institutions of learning in Southeast Nigeria region, focusing on the male and female undergraduates from these institutions as the study population. While the study was guided by Structuration Theory, survey design with questionnaire instrument was applied to manage the study and data collection procedure. Appropriate classification and statistics were applied to check the relationship of the substantive variables to the study. From the findings, there is a prevalence of acceptance of sexual harassment myths (72.3%/55.6%) among the students; gender explained 4.9%/10.4% variance of sexual harassment myths1&2, sexual harassment myths1&2 explained about 0.98%/0.22% variance of ability to report sexual harassment experience among the students. The study concludes that sexual harassment myths acceptance has been embedded in the consciousness of the youths through the overarching patriarchal structures in the system with gender-based violence and sustainable development implications.